Preparation method of fiber-reinforced zirconia powder

By doping yttrium oxide and functional metal oxides into zirconia powder and introducing surface modified ceramic fibers, the problems of unstable structure of zirconia powder and insufficient conductivity and strength toughness of zirconia powder are solved, and the stability, conductivity and strength toughness of composite zirconia powder are improved, which is suitable for a variety of high-performance ceramic applications.

CN119613112APending Publication Date: 2025-03-14JIANGSU QIHE NEW MATERIAL TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411945970.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Due to the unstable structure of the existing zirconia powder, it is prone to cracking and difficult to densely sintering, and its conductivity and strength toughness are insufficient, which limits its application in solid oxide fuel cells, oxygen sensors and other fields.

Method used

By co-doping yttrium oxide and functional metal oxide with zirconia, composite zirconia powder is prepared, and surface-modified ceramic fiber powder is introduced into the composite zirconia powder, and the strength and toughness of the powder product are improved by using the synergistic toughening effect of ceramic fibers.

Benefits of technology

The structural stability, electrical conductivity of zirconia powder and the strength and toughness of powder products have been improved, and are suitable for technical fields such as solid oxide fuel cells, special ceramics, and oxygen sensors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613112A_ABST
    Figure CN119613112A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of fiber-reinforced zirconium oxide powder. The preparation method comprises the following steps: preparing composite zirconium oxide powder co-doped with yttrium oxide and functional metal (praseodymium, scandium or cerium) oxide from soluble metal zirconium salt, soluble metal yttrium salt and functional metal salt through a hydrothermal precipitation method; wherein the yttrium oxide and the functional metal (praseodymium, scandium or cerium) oxide further improve the conductivity of the zirconium oxide powder while keeping the structural stability of the powder. And mixing the ceramic fiber powder subjected to surface pretreatment as a synergistic toughening material with the composite zirconium oxide powder, and carrying out subsequent treatment to obtain the fiber-reinforced zirconium oxide powder. By introducing the high-strength and high-toughness ceramic fiber powder into the composite zirconium oxide powder, macroscopic cracks can be blocked when penetrating through fibers, so that the strength and toughness of a powder product are improved. The fiber-reinforced zirconium oxide powder prepared by the method is uniform in particle, good in dispersity, good in stability and high in conductivity, and a powder product is high in mechanical strength and good in toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic powder material preparation, and specifically relates to a method for preparing fiber-reinforced zirconia powder. Background Art

[0002] Zirconia has been widely used in special ceramics, solid oxide fuel cells, oxygen sensors, metal oxide semiconductors, high-temperature structural materials, catalysts and other technical fields due to its advantages such as high hardness, high strength, high toughness, extremely high wear resistance, good chemical stability, thermal stability and excellent biocompatibility. Zirconia has three crystal structures: monoclinic, tetragonal and cubic. It is an oxide of polycrystalline phase transformation. However, products made of pure zirconia powder are unstable in structure due to the transformation of zirconia crystal form, and are prone to cracking and difficulty in dense sintering. In order to improve the stability of the zirconia powder structure, the researchers selected Zr 4+ Metal oxides with relatively close ionic radii, such as magnesium oxide, calcium oxide, aluminum oxide, yttrium oxide, etc., are doped and synthesized with zirconium oxide powder to keep the zirconium oxide powder in a stable structure.

[0003] With the wide application of zirconium oxide powder in the fields of solid oxide fuel cells and oxygen sensor technology, the requirements for the quality and performance of zirconium oxide powder are becoming more and more stringent. Based on the synthesis of high-quality zirconium oxide powder, the obtained powder has a small particle size, a narrow particle size distribution range, good dispersibility, high thermal stability and high electrical conductivity. Therefore, the control of the micromorphology and crystal structure of zirconium oxide powder has become a key area of ​​research in recent years. For example, patent CN113149071A provides a method for preparing a synthetic nano ZrO2 powder, using electrostatic elimination assisted homogeneous precipitation technology to make a zirconium nitrate solution and a urea solution mixed reaction, separating the precipitation solution obtained by the reaction, and obtaining a nano ZrO2 powder after heating, washing, drying and calcining. The method is simple to operate, has a small powder particle size, high activity and good dispersibility. However, the structure of pure zirconium oxide powder is unstable, which limits its application. Patent CN117886604A discloses a method for preparing yttria-stabilized zirconia powder, which utilizes the action of complexing agent and dispersant to complex zirconium and yttrium ions and then evenly distributes them in the solution, controls the pH value of the solution, adds a precipitant, obtains a zirconium-yttrium precursor powder without hard agglomeration, and finally obtains yttria-stabilized zirconia nanopowder through a calcination process. The preparation method can more easily control the particle shape and size of yttria-stabilized zirconia, and the method is simple to operate, the raw materials are easily available, and it is conducive to industrial production. However, although the single yttria-doped zirconia powder can improve the stability of the powder structure, it has little effect on improving the conductivity of the powder and the toughness and strength of the powder product. Patent CN113979770A provides a method for preparing an enhanced yttrium-stabilized nanocomposite zirconia ceramic powder. By introducing similarly compatible zirconia fibers, an enhanced composite ceramic material is prepared. The addition of zirconia fibers improves the toughness of zirconia powder materials mainly in the debonding, pull-out and bridging effects of the fibers during crack propagation. This method can improve the toughness of zirconia ceramic powder products by adding fibers, but it cannot effectively improve the conductivity of the powder and its products, limiting its application in solid oxide fuel cells, oxygen sensors and other fields. In order to improve the conductivity of zirconia powder, the researchers used a Zr 4+Metal substances with similar ionic radius are co-doped with zirconium oxide powder to prepare composite zirconium oxide powder with high conductivity and good chemical stability. For example, patent CN111592038A provides a method for preparing scandium oxide-stabilized zirconium oxide nanopowder, which adopts a uniform coprecipitation method combined with a hydrothermal method to prepare a scandium oxide-stabilized zirconium oxide nanopowder with small particle size, high conductivity and excellent high-temperature chemical stability. Patent CN107445203A first uses a template to synthesize a precursor of zirconium oxychloride with steric hindrance, and then uses a coprecipitation method to prepare scandium oxide-stabilized zirconium oxide. The prepared scandium oxide-stabilized zirconium oxide particles have good dispersibility and uniform particle size, which can effectively solve the problem that the powder is easy to agglomerate in organic slurry and has poor dispersibility, resulting in low density and low conductivity of sintered porcelain pieces. However, although zirconium oxide powder with high conductivity and good stability can be prepared by doping scandium oxide, the strength and toughness of the powder products still need to be improved. Summary of the invention

[0004] The purpose of the present invention is to combine the advantages of existing patented technologies and improve on existing technologies, and to provide a method for preparing fiber-reinforced zirconia powder with simple process, uniform powder particles and good dispersibility. The prepared zirconia powder has high electrical conductivity and good stability, and the powder products have high strength and good toughness, and can be applied to technical fields such as solid oxide fuel cells, special ceramics, and oxygen sensors.

[0005] The technical idea of ​​the present invention is: firstly, a soluble metal zirconium salt, a soluble metal yttrium salt and a functional metal salt are prepared by a hydrothermal precipitation method to obtain a composite zirconium oxide powder co-doped with yttrium oxide and a functional metal (praseodymium, scandium or cerium) oxide. Among them, yttrium oxide is a more commonly used zirconia structure stabilizing agent, which helps to form a stable crystal structure; while maintaining the stability of the powder structure, the functional metal (praseodymium, scandium or cerium) oxide further improves the conductivity of the zirconium oxide powder. Then, a surface modifier is used to perform surface modification treatment on the toughening ceramic fiber, so that the surface of the ceramic fiber is coated with the surface modifier to form a layer of polar film, which can increase the adhesion when mixed with the composite zirconium oxide powder. At the same time, the toughness of the ceramic fiber is improved. Finally, the ceramic fiber powder after surface modification pretreatment is mixed with the composite zirconium oxide powder as a synergistic toughening material, and a fiber-reinforced zirconium oxide powder is prepared after hydrothermal reaction and subsequent treatment. The present invention introduces high-strength and high-toughness ceramic fiber powder into the composite zirconium oxide powder, which can block macro cracks when passing through the fiber, thereby improving the strength and toughness of the powder product. The fiber-reinforced zirconium oxide powder prepared by the present invention has uniform particles, good dispersibility, good stability, high electrical conductivity, and the powder product has high mechanical strength and good toughness.

[0006] To achieve the above purpose, the specific technical solutions adopted by the present invention are as follows: A method for preparing fiber-reinforced zirconium oxide powder, characterized in that the method comprises the following steps: (1) Preparation of composite zirconium oxide powder: a soluble metal zirconium salt, a soluble metal yttrium salt, a functional metal salt, and a dispersant are mixed with water in a certain proportion to form a composite metal zirconium mixed solution; a precipitant is added to the composite metal zirconium mixed solution to generate a precursor precipitate; the precursor precipitate is filtered and mixed with water, the pH of the solution is adjusted to 8 to 10 to form a mixed solution, and the mixed solution is placed in a reactor for hydrothermal reaction; the reaction product is first washed with water and ethanol, and after drying, it is crushed and ground to obtain a composite zirconium oxide powder; (2) Pretreatment of ceramic fiber powder: The ceramic fiber material is mixed with the surface modification solution and stirred for surface treatment, and then the surface treated ceramic fiber material is dried and then ball milled to obtain pretreated ceramic fiber powder; (3) The composite zirconia powder obtained in the above step (1) and the pretreated ceramic fiber powder obtained in step (2) are mixed in proportion, the mixed powder is mixed with water to form a slurry, and then 15-20% by mass of hydrochloric acid is added to adjust the pH of the mixed slurry to 2-4. After the mixed slurry is evenly mixed by ball milling, it is added to a hydrothermal reactor. After the reaction is completed, the reaction product is subsequently cleaned and heat treated to obtain a fiber-reinforced zirconia powder.

[0007] Specifically, the soluble metal zirconium salt in step 1 is zirconium oxychloride, zirconium tetrachloride or zirconium nitrate; the soluble metal yttrium salt is yttrium chloride or yttrium nitrate; and the functional metal salt is one or more of praseodymium nitrate, scandium nitrate or cerium nitrate.

[0008] Furthermore, the mass ratio of the soluble metal zirconium salt to the soluble metal yttrium salt in step 1 is (1 ~ 5): (0.1 ~ 1); the mass ratio of the soluble metal zirconium salt to the functional metal salt is 1: (0.05 ~ 0.1); the mass ratio of the soluble metal zirconium salt to water is 1: (10 ~ 30). The present invention uses soluble metal salts to prepare composite zirconium oxide powders co-doped with yttrium oxide, functional metal oxides and zirconium oxide, wherein yttrium oxide helps the zirconium oxide powder to form a stable crystal structure, and at the same time, the functional metal oxide further improves the conductivity of the zirconium oxide powder while maintaining the stability of the powder structure.

[0009] Furthermore, the dispersant described in step 1 is a dispersant solution obtained by mixing polyethylene glycol or polyvinyl alcohol with water in a mass ratio of 1: (1 to 8), and the amount of the dispersant added is 0.5 to 5% of the total mass of the composite metal zirconium mixed solution; the precipitant is ammonia water or ammonium bicarbonate aqueous solution with a mass fraction of 15 to 25%.

[0010] Specifically, the hydrothermal reaction time in step 1 is 5 to 20 h; the reaction temperature is 150 to 200°C.

[0011] Specifically, the crushing and grinding treatment in step 1 is to prepare a mixed slurry with water having a mass fraction of 35 to 55% of the reaction product after washing and drying, and then ball mill the mixed slurry in a planetary ball mill at 300 to 350 r / min for 1 to 3 hours.

[0012] Specifically, the ceramic fiber material in step 2 is one or more of zirconium oxide fiber, silicon oxide fiber, and yttrium oxide fiber; the surface modification solution is a mixture of silane coupling agent (KH550) and water, and the mass fraction of silane coupling agent (KH550) in the surface modification solution is 0.5 to 1.5%; the surface treatment time is 0.5 to 1 h. In the present invention, the ceramic fiber material is surface modified by a surface modifier, and the surface modifier is coated on the surface of the ceramic fiber to form a polar film, which helps to increase the adhesion and improve the toughness of the ceramic fiber.

[0013] Furthermore, the mass ratio of the composite zirconia powder and the pretreated ceramic fiber powder in step 3 is 1: (0.01 to 0.1); the mass ratio of the mixed powder to water is 1: (1 to 2.5); the hydrothermal reaction time is 1 to 5 hours; and the reaction temperature is 150 to 200°C. The present invention mixes the composite zirconia powder with the pretreated ceramic fiber powder, and utilizes the synergistic toughening effect of the ceramic fiber to play a role in debonding, pulling out and bridging in the process of macro crack development, and the crack is blocked when passing through the fiber, thereby improving the strength and toughness of the powder product.

[0014] Specifically, the heat treatment described in step 3 is carried out under vacuum atmosphere at a temperature of 500 to 800° C. for 0.5 to 2.5 h.

[0015] The specific surface area of ​​the fiber-reinforced zirconia powder prepared by the present invention is 20.51 to 25.71 m 2 / g, the electrical conductivity of ceramic products prepared from fiber-reinforced zirconia powder at 800℃ is 0.165 ~ 0.175 S / cm, and the flexural strength is 525 ~ 600 MPa.

[0016] Compared with the prior art process, the beneficial effects of the present invention are as follows: 1. The present invention co-dopes yttrium oxide, functional metal oxides and zirconium oxide to prepare composite zirconium oxide powder with good powder dispersibility, uniform powder particles, good stability and high conductivity of powder products. Among them, yttrium oxide helps the zirconium oxide powder to form a stable crystal structure, and at the same time, the addition of functional metal oxides further improves the conductivity of the zirconium oxide powder while maintaining the stability of the powder structure.

[0017] 2. The present invention firstly performs surface modification treatment on the ceramic fiber material using a surface modifier, and the surface modifier is coated on the surface of the ceramic fiber to form a polar film, which helps to increase the adhesion and improve the toughness of the ceramic fiber. Then, the pretreated ceramic fiber powder is introduced into the composite zirconia powder, and the synergistic toughening effect of the ceramic fiber is utilized to play a role in debonding, pulling out and bridging in the process of macro crack development. When the crack passes through the fiber, it is blocked, thereby improving the strength and toughness of the powder product.

[0018] 3. The process of the present invention is simple, does not require complicated equipment, and is suitable for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the SEM image of the fiber-reinforced zirconia powder of Example 1.

[0020] Figure 2 Schematic diagram of the structure of fiber-reinforced zirconia powder.

[0021] Figure 3 This is the particle size distribution diagram of the fiber-reinforced zirconia powder in Example 1. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with specific examples, but the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry.

[0023] Example 1 An embodiment of the method for preparing the fiber-reinforced zirconia powder of the present invention comprises the following steps: (1) Preparation of composite zirconium oxide powder: 20 g of zirconium oxychloride, 4 g of yttrium chloride, and 2 g of scandium nitrate were weighed and mixed with 300 g of water, and then 1.63 g of polyethylene glycol solution (wherein the mass ratio of polyethylene glycol to water in the polyethylene glycol solution is 1:1) was added to form a composite metal zirconium mixed solution; 15% ammonia aqueous solution was added to the composite metal zirconium mixed solution to generate a precursor precipitate; the precursor precipitate was filtered and mixed with water, and the pH of the solution was adjusted to 8-10 to form a mixed solution, and the mixed solution was placed in a reactor for hydrothermal reaction at a reaction temperature of 180 °C and a reaction time of 8 h; the reaction product was first washed with water and ethanol, and after drying, the reaction product was mixed with water to form a mixed slurry with a mass fraction of 35%, and the mixed slurry was ball-milled in a planetary ball mill at 350 r / min for 1 h to obtain composite zirconium oxide powder; (2) Pretreatment of ceramic fiber powder: Zirconia fiber material with a diameter of 2 nm and an aspect ratio of 10 was mixed with 1% by mass of a silane coupling agent (KH550) for surface treatment for 1 h. The surface-treated ceramic fiber material was then dried at 90 °C and ball-milled at 350 r / min for 1 h to obtain pretreated ceramic fiber powder. (3) The composite zirconia powder obtained in the above step (1) and the pretreated ceramic fiber powder obtained in step (2) are mixed in a mass ratio of 1:0.01, and the mixed powder is mixed with water in a mass ratio of 1:1 to form a mixed slurry, and 20% hydrochloric acid is added to adjust the pH of the mixed slurry to 2. The mixed slurry is mixed evenly by ball milling, and then added to a hydrothermal reactor for reaction at a temperature of 180°C for 3 h. The reaction product is then washed with water and ethanol for 5 times, dried at 80°C, and heat treated at 800°C in a vacuum atmosphere for 2 h to obtain fiber-reinforced zirconia powder.

[0024] The specific surface area of ​​the fiber-reinforced zirconia powder prepared in this example is 20.51 m 2 / g.

[0025] Example 2 An embodiment of the method for preparing the fiber-reinforced zirconia powder of the present invention comprises the following steps: (1) Preparation of composite zirconium oxide powder: 20 g zirconium nitrate, 2 g yttrium nitrate, and 1 g cerium nitrate were weighed and mixed with 200 g water, and then 22.1 g polyvinyl alcohol solution (wherein the mass ratio of polyvinyl alcohol to water in the polyvinyl alcohol solution is 1:8) was added to form a composite metal zirconium mixed solution; 20% ammonia aqueous solution was added to the composite metal zirconium mixed solution to generate a precursor precipitate; the precursor precipitate was filtered and mixed with water, and the pH of the solution was adjusted to 8-10 to form a mixed solution, and the mixed solution was placed in a reactor for hydrothermal reaction at a reaction temperature of 150 °C and a reaction time of 20 h; the reaction product was first washed with water and ethanol, and after drying, the reaction product was mixed with water to form a mixed slurry with a mass fraction of 45%, and the mixed slurry was ball milled in a planetary ball mill at 300 r / min for 3 h to obtain composite zirconium oxide powder; (2) Pretreatment of ceramic fiber powder: Yttrium oxide fiber material with a diameter of 5 nm and an aspect ratio of 10 was mixed with 1.2% by mass of a silane coupling agent (KH550) for surface treatment for 0.5 h. The surface-treated ceramic fiber material was then dried at 90 °C and ball-milled at 300 r / min for 3 h to obtain pretreated ceramic fiber powder. (3) The composite zirconia powder obtained in the above step (1) and the pretreated ceramic fiber powder obtained in step (2) are mixed in a mass ratio of 1:0.1, and the mixed powder is mixed with water in a mass ratio of 1:1.5 to form a mixed slurry, and then 15% by mass of hydrochloric acid is added to adjust the pH of the mixed slurry to 4. The mixed slurry is mixed evenly by ball milling, and then added to a hydrothermal reactor at a temperature of 150°C. After reacting for 5 hours, the obtained reaction product is washed with water and ethanol for 5 times, dried at 70°C, and heat treated at 700°C in a vacuum atmosphere for 1.5 hours to obtain fiber-reinforced zirconia powder.

[0026] The specific surface area of ​​the fiber-reinforced zirconia powder prepared in this example is 22.37 m 2 / g.

[0027] Example 3 An embodiment of the method for preparing the fiber-reinforced zirconia powder of the present invention comprises the following steps: (1) Preparation of composite zirconium oxide powder: 26 g zirconium nitrate, 6 g yttrium nitrate, and 2.08 g cerium nitrate were weighed and mixed with 780 g water, and then 40.7 g polyvinyl alcohol solution (wherein the mass ratio of polyvinyl alcohol to water in the polyvinyl alcohol solution is 1:3) was added to form a composite metal zirconium mixed solution; 25% ammonium bicarbonate aqueous solution was added to the composite metal zirconium mixed solution to generate a precursor precipitate; the precursor precipitate was filtered and mixed with water, and the pH of the solution was adjusted to 8-10 to form a mixed solution, and the mixed solution was placed in a reactor for hydrothermal reaction at a reaction temperature of 200 °C and a reaction time of 5 h; the reaction product was first washed with water and ethanol, and after drying, the reaction product was mixed with water to form a mixed slurry with a mass fraction of 55%, and the mixed slurry was ball-milled in a planetary ball mill at 320 r / min for 2 h to obtain composite zirconium oxide powder; (2) Pretreatment of ceramic fiber powder: Silica fiber material with a diameter of 8 nm and an aspect ratio of 10 was mixed with 1.5% by mass of a silane coupling agent (KH550) for surface treatment for 0.8 h. The surface-treated ceramic fiber material was then dried at 90 °C and ball-milled at 320 r / min for 2 h to obtain pretreated ceramic fiber powder. (3) The composite zirconia powder obtained in the above step (1) and the pretreated ceramic fiber powder obtained in step (2) are mixed in a mass ratio of 1:0.05, and the mixed powder is mixed with water in a mass ratio of 1:2.5 to form a mixed slurry, and then 18% hydrochloric acid is added to adjust the pH of the mixed slurry to 3. The mixed slurry is mixed evenly by ball milling, and then added to a hydrothermal reactor at a temperature of 200°C. After reacting for 1 hour, the obtained reaction product is washed with water and ethanol for 5 times, dried at 85°C, and heat treated at 750°C in a vacuum atmosphere for 1 hour to obtain fiber-reinforced zirconia powder.

[0028] The specific surface area of ​​the fiber-reinforced zirconia powder prepared in this example is 25.71 m 2 / g.

[0029] Example 4 An embodiment of the method for preparing the fiber-reinforced zirconia powder of the present invention comprises the following steps: (1) Preparation of composite zirconium oxide powder: 30 g zirconium nitrate, 10 g yttrium nitrate, and 3 g praseodymium nitrate were weighed and mixed with 680 g water, and then 7.23 g polyvinyl alcohol solution (wherein the mass ratio of polyvinyl alcohol to water in the polyvinyl alcohol solution is 1:5) was added to form a composite metal zirconium mixed solution; 20% ammonia aqueous solution was added to the composite metal zirconium mixed solution to generate a precursor precipitate; the precursor precipitate was filtered and mixed with water, and the pH of the solution was adjusted to 8-10 to form a mixed solution, and the mixed solution was placed in a reactor for hydrothermal reaction at a reaction temperature of 170 °C and a reaction time of 10 h; the reaction product was first washed with water and ethanol, and after drying, the reaction product was mixed with water to form a mixed slurry with a mass fraction of 50%, and the mixed slurry was ball milled in a planetary ball mill at 325 r / min for 1.5 h to obtain composite zirconium oxide powder; (2) Pretreatment of ceramic fiber powder: Silica fiber material with a diameter of 3 nm and an aspect ratio of 10 was mixed with 0.5% by mass of a silane coupling agent (KH550) for surface treatment for 1 h. The surface-treated ceramic fiber material was then dried at 90 °C and ball-milled at 325 r / min for 1.5 h to obtain pretreated ceramic fiber powder. (3) The composite zirconia powder obtained in the above step (1) and the pretreated ceramic fiber powder obtained in step (2) are mixed in a mass ratio of 1:0.08, and the mixed powder is mixed with water in a mass ratio of 1:1 to form a mixed slurry, and then 18% hydrochloric acid is added to adjust the pH of the mixed slurry to 3. The mixed slurry is mixed evenly by ball milling, and then added to a hydrothermal reactor at a temperature of 170°C. After reacting for 2.5 hours, the reaction product is washed with water and ethanol for 5 times, dried at 75°C, and heat treated at 500°C in a vacuum atmosphere for 2.5 hours to obtain fiber-reinforced zirconia powder.

[0030] The specific surface area of ​​the fiber-reinforced zirconia powder prepared in this example is 21.92 m 2 / g.

[0031] Comparative Example 1 This comparative example provides a method for preparing a composite zirconium oxide powder, which is basically the same as Example 1, except that the composite zirconium oxide powder is prepared without performing steps (2) and (3).

[0032] The present invention tests the performance of the zirconium oxide powder and powder products prepared in the above Examples 1 to 4 and Comparative Example 1. The test results are shown in Table 1. The specific test method conditions are as follows: (1) Average specific surface area of ​​zirconia powder: The average specific surface area of ​​zirconia powder was measured by the BET method using nitrogen as the adsorbent.

[0033] (2) Bending strength of zirconia powder products: The zirconia powders prepared in Examples 1 to 4 of the present invention and Comparative Example 1 were first molded by isostatic pressing and kept at 1300°C for 5 h to obtain a zirconia sintered body. The zirconia sintered body was then cut into specimens with a length of 50 mm, a width of 4 mm, and a height of 4 mm. The surfaces of the specimens were polished and tested using a flexural strength tester.

[0034] (3) Electrical conductivity of zirconium oxide powder products: The zirconium oxide powders prepared in Examples 1 to 4 of the present invention and Comparative Example 1 were mixed with a dispersant, a binder, a solvent, and a plasticizer to prepare a slurry, which was then cast into a film and then sintered to obtain an electrolyte diaphragm sheet. The electrical conductivity of the electrolyte diaphragm sheet at 800° C. was tested using an electrochemical workstation.

[0035] (4) Powder particle size analysis: The particle size and particle size distribution of the zirconium oxide powders prepared in Examples 1 to 4 of the present invention and Comparative Example 1 were tested using a laser particle size analyzer.

[0036] Table 1 summarizes the performance test results of the zirconium oxide powders and powder products prepared in Examples 1 to 4 and Comparative Example 1.

[0037] Serial number <![CDATA[Average specific surface area of powder (m 2 / g)]]> Flexural strength (MPa) Conductivity (S / cm) Example 1 20.51 525 0.175 Example 2 22.37 600 0.165 Example 3 25.71 556 0.170 Example 4 21.92 578 0.175 Comparative Example 1 20.14 455 0.175

[0038] By comparing the test results of the samples of Examples 1 to 4 and Comparative Example 1, it can be seen that the present invention introduces pretreated ceramic fiber powder into the composite zirconia powder, and utilizes the synergistic toughening effect of ceramic fiber to improve the strength and toughness of the zirconia powder product. In Comparative Example 1, since no ceramic fiber powder is added to the zirconia powder, the powder product is relatively brittle and has relatively low strength and toughness. The flexural strength of the zirconia powder product in the embodiment of the present invention reaches 525 to 600 MPa.

[0039] The test results of the samples of Examples 1 to 4 and Comparative Example 1 above give the following conclusions: 1. The present invention co-dopes yttrium oxide, functional metal oxides and zirconium oxide to prepare composite zirconium oxide powder with good powder dispersibility, uniform powder particles, good stability and high conductivity of powder products. The specific surface area of ​​the fiber-reinforced zirconium oxide powder prepared by the present invention is 20.51 to 25.71 m 2 / g, the electrical conductivity of ceramic products prepared from fiber-reinforced zirconia powder at 800℃ is 0.165 ~ 0.175 S / cm, and the flexural strength is 525 ~ 600 MPa.

[0040] (2) The present invention first pre-treats the surface of the ceramic fiber powder to increase the adhesion and toughness of the ceramic fiber. Then, high-strength and high-toughness ceramic fiber powder is introduced into the composite zirconia powder to block macro cracks when passing through the fiber, thereby improving the strength and toughness of the powder product.

Claims

1. A method for preparing fiber-reinforced zirconia powder, characterized in that: The method comprises the following steps: (1) Preparation of composite zirconium oxide powder: a soluble metal zirconium salt, a soluble metal yttrium salt, a functional metal salt, and a dispersant are mixed with water in a certain proportion to form a composite metal zirconium mixed solution; a precipitant is added to the composite metal zirconium mixed solution to generate a precursor precipitate; the precursor precipitate is filtered and mixed with water, the pH of the solution is adjusted to 8 to 10 to form a mixed solution, and the mixed solution is placed in a reactor for hydrothermal reaction; the reaction product is first washed with water and ethanol, and after drying, it is crushed and ground to obtain composite zirconium oxide powder; (2) Pretreatment of ceramic fiber powder: The ceramic fiber material is mixed with the surface modification solution and stirred for surface treatment, and then the surface treated ceramic fiber material is dried and then ball milled to obtain pretreated ceramic fiber powder; (3) The composite zirconia powder obtained in the above step (1) and the pretreated ceramic fiber powder obtained in step (2) are mixed in proportion, the mixed powder is mixed with water to form a slurry, and then 15-20% by mass of hydrochloric acid is added to adjust the pH of the mixed slurry to 2-4. After the mixed slurry is evenly mixed by ball milling, it is added to a hydrothermal reactor. After the reaction is completed, the reaction product is subsequently cleaned and heat treated to obtain a fiber-reinforced zirconia powder.

2. The method for preparing fiber-reinforced zirconia powder according to claim 1, characterized in that: The soluble metal zirconium salt in step 1 is zirconium oxychloride, zirconium tetrachloride or zirconium nitrate; the soluble metal yttrium salt is yttrium chloride or yttrium nitrate; and the functional metal salt is one or more of praseodymium nitrate, scandium nitrate or cerium nitrate.

3. The method for preparing fiber-reinforced zirconia powder according to claim 1, characterized in that: The mass ratio of the soluble metal zirconium salt to the soluble metal yttrium salt described in step 1 is (1 to 5): (0.1 to 1); the mass ratio of the soluble metal zirconium salt to the functional metal salt is 1: (0.05 to 0.1); the mass ratio of the soluble metal zirconium salt to water is 1: (10 to 30).

4. The method for preparing fiber-reinforced zirconia powder according to claim 1, characterized in that: The dispersant described in step 1 is a dispersant solution obtained by mixing polyethylene glycol or polyvinyl alcohol with water in a mass ratio of 1: (1 to 8), and the amount of the dispersant added is 0.5 to 5% of the total mass of the composite metal zirconium mixed solution; the precipitant is a 15 to 25% mass fraction of ammonia water or ammonium bicarbonate aqueous solution.

5. The method for preparing fiber-reinforced zirconia powder according to claim 1, characterized in that: The hydrothermal reaction time in step 1 is 5 to 20 h; the reaction temperature is 150 to 200°C.

6. The method for preparing fiber-reinforced zirconia powder according to claim 1, characterized in that: The crushing and grinding treatment described in step 1 is to prepare a mixed slurry with a mass fraction of 35 to 55% by weight of the reaction product after washing and drying with water, and then ball mill the mixed slurry in a planetary ball mill at 300 to 350 r / min for 1 to 3 hours.

7. The method for preparing fiber-reinforced zirconia powder according to claim 1, characterized in that: The ceramic fiber material described in step 2 is one or more of zirconium oxide fiber, silicon oxide fiber, and yttrium oxide fiber; the surface modification solution is a mixture of a silane coupling agent (KH550) and water, and the mass fraction of the silane coupling agent (KH550) in the surface modification solution is 0.5 to 1.5%; the surface treatment time is 0.5 to 1 h.

8. The method for preparing fiber-reinforced zirconia powder according to claim 1, characterized in that: The mass ratio of the composite zirconia powder and the pretreated ceramic fiber powder in step 3 is 1: (0.01 to 0.1); the mass ratio of the mixed powder to water is 1: (1 to 2.5); the hydrothermal reaction time is 1 to 5 hours; and the reaction temperature is 150 to 200°C.

9. The method for preparing fiber-reinforced zirconia powder according to claim 1, characterized in that: The heat treatment described in step 3 is carried out under vacuum atmosphere at a temperature of 500 to 800° C. for 0.5 to 2.5 h.

Citation Information

Patent Citations

  • Scandium oxide stabilized zirconium oxide, and preparation method thereof

    CN107445203A

  • Preparation method for synthesizing nano ZrO2 powder

    CN113149071A

  • Preparation method of enhanced yttrium-stabilized nano-composite zirconia ceramic powder

    CN113979770A

  • Preparation method of yttrium oxide stabilized zirconium oxide powder

    CN117886604A